Aiming to induce broadly reactive neutralizing antibody responses with HIV-1 vaccine candidates - Haynes, Barton F (2006)
Neutralizing antibody induction is a key feature of many effective vaccines and is the only immune response that has proven to be capable of completely blocking AIDS virus infection in animal models. Unfortunately, the extensive genetic variability and complex immune-evasion strategies of HIV-1 have thwarted all attempts to date at eliciting an effective neutralizing antibody response with candidate HIV-1 vaccine immunogens. Recent advances in our understanding of how these evasion strategies operate, coupled with growing progress in unravelling the structure and immunobiology of the viral envelope glycoproteins, are contributing to novel immunogen designs to overcome the many barriers to inducing protective antibodies against HIV-1.